FIRST-ROW TRANSITION METAL COMPLEXES OF OMEPRAZOLE AS ANTI-ULCERATIVE DRUGS - Suman Malik; Supriya Das; Bharti Jain (Indonesian Journal of Chemistry, 2010)
Omeprazole (OME) is a proton pump inhibitor (PPI). PPIs have enabled to improve the treatment of various acid-peptic disorders. OME is a weak base and it can form several complexes with transition and non-transition metal ions. In the present paper, we are describing series of transition metal complexes of omeprazole i.e., 5-methoxy-2[(4methoxy-3, 5dimethyl-2-pyridinyl) methylsulfinyl]-1H-benzimidazole with CuII, MnII, CoII, NiII, FeII, ZnII andHgII. These complexes were characterized by elemental analysis, molar conductivity, IR, NMR, magnetic susceptibility, UV-visible spectral studies, ESR, SEM and X-ray diffraction. Based on the above studies, the ligand behaves as bidentate O, N donor and forms coordinate bonds through C=N and S=O groups. The complexes were found to non-electrolytic in nature on the basis of low values of molar conductivity. Analytical data and stoichiometry analysis suggest ligand to metal ratio of 2:1 for all the complexes. Electronic spectra and magnetic susceptibility measurements reveal octahedral geometry for Mn(II),Co(II), Ni(II),Fe(II) and Cu(II) complexes and tetrahedral for Hg(II) and Zn(II) complexes. Ligands and their metal complexes have been screened for their antibacterial and antifungal activities against bacteria Pseudomonas, Staphylococcus aureus and fungi Aspergillus niger and A. flavous.